Ethnic differences in fetal size and growth in a multi-ethnic population. Issue 9 (September 2015) - Sletner, Line; Rasmussen, Svein; Jenum, Anne Karen; Nakstad, Britt; Jensen, Odd Harald Rognerud; Vangen, Siri
Abstract Objectives Impaired or excessive fetal growth is associated with adverse short- and long-term health outcomes that differ between ethnic groups. We explored ethnic differences in fetal size and growth from mid pregnancy until birth. Methods Data are from the multi-ethnic STORK-Groruddalen study, a population-based, prospective cohort of 823 pregnant women and their offspring in Oslo, Norway. Measures were z-scores of estimated fetal weight (EFW), head circumference (HC), abdominal circumference (AC) and femur length (FL), in gestational week 24, 32 and 37, measured by ultrasound, and similar measures at birth. Differences in fetal size and growth were assessed using separate Linear Mixed Models including all four time points, with ethnic Europeans as reference. Results In week 24 South Asian fetuses had smaller AC, but larger FL than Europeans, and slightly lower EFW (− 0.17 SD (− 0.33, − 0.01), p = 0.04). Middle East/North African fetuses also had larger FL, but similar AC, and hence slightly higher EFW (0.18 (0.003, 0.36), p = 0.05). Both groups had slower growth of AC, FL and EFW from this time until birth, and had − 0.61 SD (− 0.73, − 0.49) and − 0.28 SD (− 0.41, − 0.15) lower birth weight respectively. Ethnic East Asians, on the other hand, were smaller throughout pregnancy and had − 0.58 SD (− 0.82, − 0.34) lower birth weight. Significant ethnic differences remained after adjusting for maternal factors. Conclusion We observed ethnic differences in fetal size and body proportions already in gestational week 24, and in fetal growth from this time until birth, which were only partly explained by key maternal factors.